Fe biomineralization mirrors individual metabolic activity in a nitrate-dependent Fe(II)-oxidizer - MIOT, Jennyfer; Remusat, Laurent; Duprat, Elodie; Gonzalez, Adriana; Pont, Sylvain; Poinsot, Melanie (Frontiers in Microbiology, 2015)
Microbial biomineralization sometimes leads to periplasmic encrustation, which is predicted to enhance microorganism preservation in the fossil record. Mineral precipitation within the periplasm is, however, thought to induce death, as a result of permeability loss preventing nutrient and waste transit across the cell wall. This hypothesis had, however, never been investigated down to the single cell level. Here, we cultured the nitrate reducing Fe(II) oxidizing bacteria Acidovorax sp. strain BoFeN1 that have been previously shown to promote the precipitation of a diversity of Fe minerals (lepidocrocite, goethite, Fe phosphate) encrusting the periplasm. We investigated the connection of Fe biomineralization with carbon assimilation at the single cell level, using a combination of electron microscopy and Nano-Secondary Ion Mass Spectrometry. Our analyses revealed strong individual heterogeneities of Fe biomineralization. Noteworthy, a small proportion of cells remaining free of any precipitate persisted even at advanced stages of biomineralization. Using pulse chase experiments with 13C-acetate, we provide evidence of individual phenotypic heterogeneities of carbon assimilation, correlated with the level of Fe biomineralization. Whereas non- and moderately encrusted cells were able to assimilate acetate, higher levels of periplasmic encrustation prevented any carbon incorporation. Carbon assimilation only depended on the level of Fe encrustation and not on the nature of Fe minerals precipitated in the cell wall. Carbon assimilation decreased exponentially with increasing cell-associated Fe content. Persistence of a small proportion of non-mineralized and metabolically active cells might constitute a survival strategy in highly ferruginous environments. Eventually, our results suggest that periplasmic Fe biomineralization may provide a signature of individual metabolic status, which could be looked for in the fossil record and in modern environmental samples.